Epidemiologia da infecção genital pelo Papilomavírus humano (HPV) em população feminina geral e população carcerária - PLÁCIDO, Waléria da Silva (Universidade Federal do Pará, 2013)
The genital infection by human papillomavirus (HPV) is considered a sexually transmitted diseases (STD) more common, representing an important problem in Public Health, in addition to being directly related to promotion of cervix cancer. This study was to investigate the epidemiological aspects of genital infection by HPV into two distinct groups: Women of general population and incarcerated women. For both a cross-sectional study was conducted analytical with 423 women from the age of 18 years who underwent preventive examination of cancer of the uterine cervix being 233 women of the general population from a basic health unit of the city of Belem and 190 from the Rehabilitation Center in female Ananindeua in the same State In the period from January 2008 to March 2010. Samples of the uterine cervix were collected for the achievement of conventional pap tests and for the detection of HPV DNA by polymerase chain reaction (PCR) mediated by oligonucleotide universal primers MY9/11. All the women answered a form clinical and epidemiological. Among the 423 women surveyed, the overall prevalence of genital infection by HPV was 13,0 % with a variation of 15,0 % for the general sample and 10,5 % for the prison. The most affected age group was 13 to 25 years (19 %) in the overall sample; And in women with 45 years or more (21,1 % ), in prison. Abnormalities Colpocitologics, marital status, number of new sexual partners the use of oral contraceptives, history of STDS and genital symptoms, in addition to current smoking, were factors that were associated with associated with genital HPV infection by Differently Between samples of the General Population and prison.